2018
DOI: 10.1136/jmedgenet-2018-105650
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the phenotype and mode of inheritance of patients with inherited peripheral neuropathies carrying MME mutations

Abstract: BackgroundMutations in the metalloendopeptidase (MME) gene were initially identified as a cause of autosomal recessive Charcot-Marie-Tooth disease type 2 (CMT2). Subsequently, variants in MME were linked to other late-onset autosomal dominant polyneuropathies. Thus, our goal was to define the phenotype and mode of inheritance of patients carrying changes in MME.MethodsWe screened 197 index cases with a hereditary neuropathy of the CMT type or distal hereditary motor neuropathy (dHMN) and 10 probands with famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Clinical data of index patients are displayed in Table S1, S3-S4 and are summarized in Table 4. Consistent with previous reports [10][11][12]25 , patients with MME variants from our study generally presented with a uniform, recognizable phenotype. Despite advanced age at onset, the neuropathy was rather severe and rapidly progressive, leading to muscle wasting and weakness predominantly in the lower legs (particularly loss of foot dorsiflexion, Fig.…”
Section: Clinical Manifestations Of Mme Variantssupporting
confidence: 92%
See 1 more Smart Citation
“…Clinical data of index patients are displayed in Table S1, S3-S4 and are summarized in Table 4. Consistent with previous reports [10][11][12]25 , patients with MME variants from our study generally presented with a uniform, recognizable phenotype. Despite advanced age at onset, the neuropathy was rather severe and rapidly progressive, leading to muscle wasting and weakness predominantly in the lower legs (particularly loss of foot dorsiflexion, Fig.…”
Section: Clinical Manifestations Of Mme Variantssupporting
confidence: 92%
“…obvious that only a particular subset of rare missense variants might be causative: Nonsegregation was demonstrated for the MME variant p.Glu441Lys found in one family and for other unconvincing variants, which were mild or relatively frequent in databases 25 While heterozygous MME variants were penetrant in a considerable proportion of confirmed or suspected carriers mainly from central Europe (this series), non-penetrance of heterozygous MME variants was reported in families from Spain and Japan 10,25 . Significant variability of penetrance amongst families with distinct geographic origin has been observed in other genetic diseases like familial amyloid polyneuropathy where penetrance of TTR variants is highly population-specific [41][42] .…”
Section: A C C E P T E Dmentioning
confidence: 66%
“…However, autosomal‐dominant variants of MME were linked to patients with late adult‐onset muscle weakness, muscle cramps, gait abnormalities with wheelchair dependence occasionally, and sensory disturbances . Patients with heterozygous variants (c.466delC or c.674G>C) reported by Auer‐Grumbach et al or Lupo et al also showed muscle cramps in legs, fasciculation, distal lower limb weakness, stepagge gait, and very mild or negative distal sensory loss, suggesting that MME variants might be linked to a possibility of dHMN in those patients . dHMN shows apparent phenotypic overlap with CMT2, and also with proximal SMA, motor neuron diseases, hereditary spastic paraplegias, and other neurologic abnormalities .…”
Section: Discussionmentioning
confidence: 97%
“…The defects of MME have been identified in patients with autosomal dominant or recessive CMT2 . Autosomal‐recessive variants of MME cause late‐onset CMT2, which displays as adult‐onset progressive weakness and atrophy of distal limb muscles, gait disturbance without wheelchair dependence, and sensory disturbance of the distal limbs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation